Understanding how utilisation of mobile applications as part of an omni-channel strategy can lead to value creation for traditional brick-and-mortar retailers in South Africa - Whittaker, Louise (University of Pretoria, 2018)
Mini Dissertation (MBA)--University of Pretoria, 2017.